SCREENING OF KETOTIFEN FOR ITS ANTI-INFLAMMATORY POTENTIAL IN ALBINO RATS - M. BRAHADEESH,; M. MATHIVANI,; R. N. SURESHA,; RAJ KISHORE MAHATO, (International Journal of Pharma and Bio Sciences, 2015)
The study is about the anti-inflammatory activity of ketotifen in acute and sub acute animal model. Adult albino rats of either sex weighing 150-200 grams were randomly divided into 3 groups of 6 animals in each. The control, the standard and the test group received Gum acacia (1ml of 1%), indomethacin 8 mg/kg and ketotifen 0.36 mg /kg respectively. Acute inflammatory activity was assessed by carageenan induced paw oedema, Turpentine induced arthritis and sub acute activity was assessed by cotton pellet induced granuloma model. In carageenan induced paw oedema model, percentage of inhibition of paw oedema (anti-inflammatory activity) by indomethacin and ketotifen with respect to control were 48% and 38% respectively and the test group was 77.5% of standard.The percentage of inhibition of knee arthritis by ketotifen with respect to control and standard were 60% and 40% respectively and the test group was 67.1% of standard. The percentage of inhibition of granuloma by standard and ketotifen were 49% and 34% respectively and the test group was 77.7% of standard. In this study ketotifen showed significantly good anti-inflammatory activity in carageenan induced paw model and cotton pellet induced granuloma model and good anti-inflammatory activity in turpentine induced arthritis model. It can be a promising antiinflammatory agent in inflammatory conditions apart from its conventional use in bronchial asthma.